KOMUNIKASI KELUARGA UNTUK MEMOTIVASI TANGGUNG JAWAB ANAK BELAJAR DI MASA PANDEMI - Ghozi Garbo Sumarsono; Agus Naryoso (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2022)
The emergence of the COVID-19 pandemic has changed all aspects of Indonesian people's lives, one of which is education. This change began to be felt since the implementation of the